PENGARUH KETERSEDIAAN SARANA PRASARANA, PEMBERIAN INSENTIF, DAN PROMOSI JABATAN TERHADAP KINERJA PEGAWAI DI DINAS PERHUBUNGAN KABUPATEN BULELENG - Kartika, Riana Dewi; Irayani, Putu Anik (Universitas Panji Sakti, 2025)
This study aims to determine how the influence of the Availability ofInfrastructure Facilities, Provision of Incentives, and Promotion of Positions onEmployee Performance at the Transportation Office of Buleleng Regency. Thisstudy used a quantitative approach with the data collection technique used is aphysical questionnaire and is assisted by Civil Servants of the Buleleng RegencyTransportation Office. The measuring instrument used in the questionnaire is aLikert scale of 1-5. The selection of respondents used the Saturated Samplingmethod, namely the sampling technique as a whole from the total population,which was selected to be the respondent in this study were all Civil Servants at theTransportation Office of Buleleng Regency with a total of 82 Civil Servants. Thedata analysis technique used in this research is the SPSS version 18 model. Theresults showed that the Availability of Infrastructure Facilities, Provision ofIncentives, and Position Promotion had a positive and significant effect onEmployee Performance at the Transportation Office of Buleleng Regency.